Autochthonous carbon loading of macroalgae stimulates benthic biological nitrogen fixation rates in shallow coastal marine sediments - Raut, Yubin; Barr, Casey R.; Paris, Emily R.; Kapili, Bennett J.; Dekas, Anne E.; Capone, Douglas G. (Frontiers in Microbiology, 2024)
Macroalgae, commonly known as seaweed, are foundational species in coastal ecosystems and contribute significantly to coastal primary production globally. However, the impact of macroalgal decomposition on benthic biological nitrogen fixation (BNF) after deposition to the seafloor remains largely unexplored. In this study, we measure BNF rates at three different sites at the Big Fisherman’s Cove on Santa Catalina Island, CA, USA, which is representative of globally distributed rocky bottom macroalgal habitats. Unamended BNF rates varied among sites (0.001 – 0.05 nmol N g-1 h -1) and were generally within the lower end of previously reported ranges. We hypothesized that the differences in BNF between sites were linked to the availability of organic matter. Indeed, additions of glucose, a labile carbon source, resulted in 2 – 3 orders of magnitude stimulation of BNF rates in bottle incubations of sediment from all sites. To assess the impact of complex, autochthonous organic matter, we simulated macroalgal deposition and remineralization with additions of brown (i.e., Macrocystis pyrifera, Dictyopteris), green (i.e., Codium fragile), and red (i.e., Asparagopsis taxiformis) macroalgae. While brown and green macroalgal amendments resulted in 53 – 520-fold stimulation of BNF rates – comparable to the labile carbon addition – red alga was found to significantly inhibit BNF rates. Lastly, we employ nifH sequencing to characterize the diazotrophic community associated with macroalgal decomposition. We observed a distinct community shift in potential diazotrophs from primarily Gammaproteobacteria in the early stages of remineralization to a community dominated by Deltaproteobacteria (e.g., sulfate reducers), Bacteroidia, and Spirochaeta towards the latter phase of decomposition of brown, green, and red macroalgae. Notably, the nifH-containing community associated with red macroalgal detritus was distinct from that of brown and green macroalgae. Our study suggests coastal benthic diazotrophs are limited by organic carbon and demonstrates a significant and phylum-specific effect of macroalgal loading on benthic microbial communities.